Impact of Rare Bleeding Disorders during Pregnancy on Maternal and Fetal Outcomes: Review of 29 Pregnancies at a Single Center - Orgul, Gokcen; Aktoz, Fatih; Beksac, M. Sinan (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Objective This study aims to give information about the relationship between different types of factor deficiencies and maternal/obstetric outcomes.Methods We retrospectively reviewed the medical records of eight women with factor deficiency disorders. The demographic and clinical features of the patients after their last pregnancies were registered retrospectively.Results There were 29 pregnancies among the 8 patients. The spontaneous abortion rate was relatively high in two patients with factor XIII deficiency (80% and 57.1%) compared with the other factor deficiency groups. There were 16 births, which included 1 set of twins, and 2 deaths (1 stillbirth and 1 postpartum exitus occurred in the same patient). Intrauterine growth restriction was noted in five cases; four of these occurred in factor X deficiency cases. The mean decrease in hemoglobin level of all patients after birth was 1.7 g/dL (range, 0.2–3.6 g/dL). Red blood cell transfusion was required only in one case of factor XIII deficiency.Conclusions There is currently no consensus on the pregnancy management of women with factor deficiencies because of the limited knowledge due to the rarity of such disorders. Labor should be managed in a dedicated unit with a team consisting of an obstetrician, a hematologist, an anesthesiologist, a midwife, and a pediatrician to minimalize the complications.
Keywords: factor VII deficiency; factor X deficiency; factor XI deficiency; factor XIII deficiency; hemophilia A; pregnancy with hematologic complications